H∞ control for uncertain linear system over networks with Bernoulli data dropout and actuator saturation. (March 2018) - Yu, Jimin; Yang, Chenchen; Tang, Xiaoming; Wang, Ping
Abstract: This paper investigates the H ∞ control problems for uncertain linear system over networks with random communication data dropout and actuator saturation. The random data dropout process is modeled by a Bernoulli distributed white sequence with a known conditional probability distribution and the actuator saturation is confined in a convex hull by introducing a group of auxiliary matrices. By constructing a quadratic Lyapunov function, effective conditions for the state feedback-based H ∞ controller and the observer-based H ∞ controller are proposed in the form of non-convex matrix inequalities to take the random data dropout and actuator saturation into consideration simultaneously, and the problem of non-convex feasibility is solved by applying cone complementarity linearization (CCL) procedure. Finally, two simulation examples are given to demonstrate the effectiveness of the proposed new design techniques. Highlights: An uncertain networked control system with data dropout and actuator saturation is established. An observer-based H ∞ output feedback controller is designed. Cone complementarity linearization (CCL) procedure is exploited to solve the non-convex matrix inequalities. Simulations show the effectiveness of the proposed control scheme.